ChemInform Abstract: Low Temperature Synthesis and Structures of Alkaline Earth Metal Chalcogenides Ba3Cu4SbS6OH, BaCuSbS3 and BaCu2S2. Issue 48 (2nd December 2014) - Ma, Zhimin; Weng, Fan; Wang, Qiuran; Tang, Qun; Zhang, Ganghua; Zheng, Chong; Han, Ray P. S.; Huang, Fuqiang
Abstract A mixture of Ba3Cu4SbS6OH (I) and BaCuSbS3 (II) is hydrothermally synthesized by reaction of Cu, Sb, S, and Ba(OH)2 in H2O (autoclave, 200 °C, 48—82 h).